Evaluation of clinical, diagnostic features and therapeutic outcome of neurobrucellosis: a case series and review of literature. (17th October 2022) - Patra, Sudipta; Kalwaje Eshwara, Vandana; Pai, Aparna Ramakrishna; Varma, Muralidhar; Mukhopadhyay, Chiranjay
Abstract: Aim: In this study, we aimed to discuss the clinical features, laboratory findings, treatment and outcome of seven cases of neurobrucellosis from a tertiary care center and review the available global literature. Materials and methods: The diagnosis of neurobrucellosis was established using the following criteria in our setting: (1) signs and symptoms of neurological infection with examination of cerebrospinal fluid (CSF) revealing signs of meningitis, (2) isolation of Brucella spp. from blood and/or CSF and/or antibody titer ≥1:160 in serum using standard agglutination test (SAT) and/or the presence of anti-Brucella antibodies in CSF and/or detection of Brucella spp.-specific DNA from CSF using PCR. A literature search was performed to review previous cases of neurobrucellosis published worldwide during the last 30 years. Results: The proportion of neurobrucellosis was 2.8% in our setting. Fever with headache and altered sensorium were the major presenting complaints. Brucella melitensis was isolated from blood culture in 6 patients. From the literature search, a total of 221 cases of neurobrucellosis were reviewed and analyzed. Meningitis (32.6%), loss of hearing (25.8%) and encephalitis (14.9%) were the most common clinical features. Involvement of cranial nerves, polyradiculopathy and paraplegia were the major complications found in patients with neurobrucellosis. Conclusions: Neurobrucellosis should always be considered in the differential diagnosis of befitting neurological, rheumatological, and neuropsychiatric presentations in endemic regions for brucellosis. To prevent morbidity and mortality associated with neurobrucellosis, a multimodal diagnostic approach is essential for early and accurate diagnosis and effective treatment.